Analysis of Applied Manga Visual Style in an Audio Visual Advertisement: Indomie x Pop Mie Tori Kara Flavour (2024) - Saffanah Azka Adie; Hafiz Aziz Ahmad (Institut Seni Indonesia Yogyakarta, 2025)
Indomie released a spicy version of the premium instant ramen collection– Tori Kara flavor– in January 2024. While it serves as an addition to the initial release of the first three ramen flavors, it was advertised with Manga Visual style, unlike any other Indomie promotional releases. The advertisement was analyzed using 8 manga visual story telling techniques to further observe the role of Japanese art mediums for a non-Japanese target audience, in this case for Indonesian audiences. The role of characters, facial expressions, poses, expressive effects and motion, sense of place, world details, wordless panels and aspect-to-aspect transitions, and genre maturity creates an immersive effect towards Indonesian audience to experience a Japanese-inspired product. A big portion of Japanese visual keys was retained, with explicit and implicit behaviours still recognizable to Indonesian audiences, hence catching adolescents’ attention and increasing the level of immersiveness while watching the advertisement.